The innate immune system in SLE: type I interferons and dendritic cells - Rönnblom, L (2008)
Patients with systemic lupus erythematosus (SLE) have an increased expression of type I interferon (IFN) regulated genes because of a continuous production of IFN-α. The cellular and molecular background to this IFN-α production has started to be elucidated during the last years, as well as the consequences for the innate and adaptive immune systems. Plasmacytoid dendritic cells (pDC) activated by immune complexes containing nucleic acids secrete type I IFN in SLE. Type I IFN causes differentiation of monocytes to myeloid-derived dendritic cell (mDC) and activation of auto-reactive T and B cells. A new therapeutic option in patients with SLE is, therefore, inhibition of IFN-α, and recent data from a phase I clinical trial suggests that administration of neutralizing monoclonal antibodies against anti-IFN-α can ameliorate disease activity.